Design of Unique Auto Disconnect Password Generation for Public Wi-Fi Routers - Ms.Aishwarya Hiremath C, Ms.Sinduja J, Mr.T.M.Hayath, Ms.Akhila Kurni, (International Journal of Scientific Research and Management (IJSRM), 2017)
WI-FI has emerged as the single most popular wireless network protocol of the 21st century. While other wireless protocols work better in certain situations, WI-FI technology is used in many organizations and in other public places which often provide free access to wireless internet hotspots. Wi-Fi networks are prone to virus attacks.  Wi-Fi Protected Setup (WPS) contains a design error that could allow a weaker-than-expected defense against brute-force attacks, which could allow an attacker to gain unauthorized access to the affected system. Do note that brute-force attack is a programme that hackers often use to crack and stealthily enter into an encrypted and password protected system. Usually, users in India opt the WPS method to set up a wireless router for home network. In this method, the standard requires a PIN to be used during the setup phase. By design this method is susceptible to brute force attacks against the PIN, said the agency in an advisory issued with high severity ratings.An unauthenticated, remote attacker within range of the wireless point could use the PIN to gain unauthorized to the device to retrieve the password for the wireless network or change the configuration of the device.  It also said that some WPS devices in the country do not implement any kind of lockout policy for brute-force attempts, which greatly reduces the time to perform a successful attack.  Hence to avoid such circumstances, in this paper, we are implementing unique (one time password) key generation method. Each OTP assigned with fixed sessions. During those sessions it is allowed to access an internet until session ends. Once if session expires, it gets disconnect automatically. Hence enhancing security in Public Wi-Fi and provides an open option for researchers to implement various applications in such technologies